Targeting splicing-derived neoantigens for precision cancer immunotherapy - Mutian Tang; H. Leighton Grimes; Nathan Salomonis (Frontiers in Immunology, 2026)
Aberrant pre-mRNA splicing in cancer generates protein sequences that are rare or absent in normal tissues, creating a rich source of tumor-specific neoantigens for immunotherapy. These splicing-derived neoantigens arise through diverse mechanisms, including recurrent somatic mutations in core spliceosome components ( SF3B1 , SRSF2 , U2AF1 , and ZRSR2 ), epigenetic derepression of transposable elements that give rise to chimeric exon-TE junctions, and coordinated dysregulation of splicing regulatory networks in cancers lacking spliceosome coding mutations. These processes produce two major classes of immunotherapeutic targets: 1) MHC class I-restricted neopeptides that can be recognized by T-cell-based therapies, and 2) extracellular neoepitopes (ExNeoEpitopes) within transmembrane proteins that are accessible to HLA-independent antibody-based modalities, including monoclonal antibodies (mAbs), bispecific engagers (BiTEs), antibody-drug conjugates (ADCs), and chimeric antigen receptor (CAR)-T or CAR-NK cells. Despite their strong immunogenic potential, effective therapeutic exploitation requires overcoming key immunological barriers, including T-cell exhaustion, impaired antigen presentation through MHC-I downregulation, and suppression within the tumor microenvironment. Recent advances in computational neoantigen prediction, immunopeptidomics, surface proteomics, long-read and single-cell isoform sequencing, and AI-guided therapeutic design are enabling more systematic discovery and validation of splicing-derived targets. This review integrates current understanding of the biological origins, immunological barriers, target classes of splicing neoantigens, and the technologies that enable their advancement in cancer immunotherapy.